Geopolymer-based fully-recycled concrete and preparation method thereof

By using recycled aggregates and slag in concrete and adding sisal fibers, the problems of large carbon emissions and low strength of existing concrete materials have been solved, and the preparation of low-carbon and low-thermal conductivity of geopolymer-based fully recycled concrete has been achieved, which has improved the sustainability of the construction industry.

CN119735393APending Publication Date: 2025-04-01TONGJI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411880203.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing concrete materials emit large carbon in the production process, and the strength and toughness of recycled concrete materials are low, making it difficult to meet the sustainable needs of the construction industry.

Method used

Geopolymer-based fully recycled concrete is used to replace natural aggregates by using regenerated coarse and fine aggregates, combining slag and recycled powder as alkali-exciting precursors, and blending sisal fibers to enhance the toughness and thermal performance of the material.

Benefits of technology

The preparation of low-carbon and low-thermal conductivity of geopolymer-based fully recycled concrete has been achieved, which significantly reduces carbon emissions, improves the strength and toughness of the material, and enhances the sustainability of the construction industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735393A_ABST
    Figure CN119735393A_ABST
Patent Text Reader

Abstract

The invention relates to low-carbon low-thermal-conductivity geopolymer-based fully-recycled concrete and a preparation method thereof. The low-carbon low-thermal-conductivity geopolymer-based fully-recycled concrete comprises the following components in parts by weight: 400-500 parts of blast furnace slag; 25 to 90 parts of regenerated powder; 400 to 500 parts of recycled fine aggregate; 900 to 1000 parts of recycled coarse aggregate; 4-20 parts of sisal fiber; 200 to 250 parts of an alkali excitation liquid; 90 to 118 parts of water; 5-12 parts of a water reducing agent; and 1-4 parts of a retarder. The alkali excitation liquid comprises 135 parts of water glass and 90 parts of sodium hydroxide solution. Compared with the prior art, the recycled coarse aggregate and the recycled fine aggregate are used for replacing natural gravel aggregate, the slag and the recycled powder are mixed to serve as an alkali-activated precursor, and the chopped sisal fibers are doped to guarantee the toughness and the crack resistance of the concrete; the invention provides an application scheme for preparing geopolymer fully-recycled concrete by effectively absorbing building solid wastes and recycling a large amount of recycled concrete powder and sisal fibers, mainly focuses on'waste-free city 'construction, increases the utilization efficiency of the building wastes and industrial solid wastes, creates low-carbon low-thermal-conductivity concrete, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of building materials, and relates to a geopolymer-based fully recycled concrete and a preparation method thereof, and specifically relates to a low-carbon and low-thermal-conductivity geopolymer-based fully recycled concrete and a preparation method thereof. Background Art

[0002] Cement is the main cementing material for concrete and is produced in huge quantities. Cement production is accompanied by high energy consumption and high emissions. It is estimated that the CO generated by the cement industry is 2 Total accounts for the global CO 2 6%-7% of total emissions. Therefore, it is urgent to introduce a low-carbon cementitious material. Studies have shown that geopolymers can make full use of solid waste as raw materials and effectively reduce carbon emissions. Geopolymer is an inorganic polymer mainly composed of aluminosilicates. In engineering research, the materials used to form geopolymers are usually industrial aluminosilicate wastes, such as fly ash, rice husk ash and blast furnace slag. Compared with cement, geopolymers as cementitious materials can reduce carbon emissions by 70%-90%. On the other hand, with the advancement of urbanization, large-scale construction and demolition (C&D) waste has been generated. my country generates more than 2.35 billion tons of C&D waste each year. Using C&D waste to produce recycled aggregates can not only solve the problem of C&D waste treatment, but also alleviate the over-exploitation of natural sand and gravel, avoid the corresponding long-distance material transportation, and reduce carbon emissions during the construction process. The preparation of geopolymer fully recycled concrete can realize the high-value utilization of all components of construction solid waste. However, the problems of reduced strength, toughness and high shrinkage caused by the attachment of recycled materials to old mortar have become key problems. Fiber reinforcement is a scientific modification method to address the above-mentioned problems. Sisal fiber has the characteristics of low cost and low carbon, and is expected to become the preferred fiber to solve the strength and toughness problems of recycled concrete materials, thereby reducing carbon emissions while improving material performance. Summary of the invention

[0003] The purpose of the present invention is to provide a low-carbon and low-thermal-conductivity geopolymer-based fully recycled concrete and its preparation method, which uses recycled coarse and fine aggregates to replace natural aggregates, uses slag and recycled powder as alkali-activated precursors, and adds sisal fibers to obtain a concrete that not only has effective improvement in toughness and thermal properties, but also has an extremely low carbon footprint. It is used to improve the existing concrete's significant brittleness and large production carbon emissions, and improve the sustainability of the construction industry.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] The present invention provides a geopolymer-based fully recycled concrete, comprising the following components and their contents in parts by weight:

[0006]

[0007] Further preferably, the geopolymer-based fully recycled concrete comprises the following components and their contents in parts by weight:

[0008]

[0009] Furthermore, the alkaline stimulating liquid comprises water glass and sodium hydroxide solution, the mass ratio of the sodium hydroxide solution to the water glass is 2:3; the modulus of the water glass is 3.3; and the concentration of the sodium hydroxide solution is 10 mol / L.

[0010] Furthermore, the alkaline stimulating solution comprises the following weight parts of water glass and sodium hydroxide solution:

[0011] 120-150 parts of water glass;

[0012] 80-100 parts of sodium hydroxide solution.

[0013] Further preferably, the alkaline stimulating solution comprises the following weight portions of water glass and sodium hydroxide solution:

[0014] 135 parts of water glass;

[0015] 90 parts of sodium hydroxide solution.

[0016] Furthermore, the SiO in the water glass 2 and Na 2 The mass fraction of O is not less than 25% and 8% respectively.

[0017] Furthermore, in the water glass, according to the mass ratio, Na 2 O=8.54%,SiO 2 =27.30%, H 2 O=64.16%.

[0018] Furthermore, the blast furnace slag is S95 grade ore powder with a density of ≥2800kg / m 3 .

[0019] Furthermore, the 7d activity index of the blast furnace slag is not less than 75%, and the 28d activity index is not less than 95%.

[0020] Furthermore, the recycled powder and recycled fine aggregate are powders obtained by grinding and screening recycled concrete aggregates, the particle size of the recycled powder is ≤0.075mm, and the particle size of the recycled fine aggregate is 0.15-2.36mm; the recycled coarse aggregate is powder obtained by screening recycled concrete aggregates, and the particle size of the recycled coarse aggregate is 5-10mm.

[0021] Furthermore, the mass ratio of the blast furnace slag to the recycled powder is 9:1.

[0022] Furthermore, the particle gradation of the recycled fine aggregate is in gradation zone 2. The gradation zone 2 is the specification for particle gradation of recycled fine aggregate in GBT25176-2010 "Recycled Fine Aggregate for Concrete and Mortar".

[0023] Furthermore, the recycled coarse aggregate is a single-grade recycled concrete aggregate.

[0024] Furthermore, the sisal fiber is short-cut sisal fiber, the length of the sisal fiber is 5-20 mm, the tensile strength of the sisal fiber is ≥600 MPa, and the elastic modulus is ≥30 GPa. Preferably, the length of the sisal fiber is 5 mm, 10 mm and 20 mm.

[0025] Further preferably, the length of the sisal fiber is 5 mm and 10 mm.

[0026] Furthermore, the volume content of the sisal fiber is 0.5%-2% of the geopolymer fully recycled concrete.

[0027] Further preferably, the volumetric content of the sisal fiber is 0.5%-1% of the geopolymer fully recycled concrete.

[0028] Further preferably, when the length of the sisal fiber is 5 mm, the volumetric dosage of the sisal fiber is 1% of the geopolymer fully recycled concrete.

[0029] Further preferably, when the length of the sisal fiber is 10 mm, the volumetric dosage of the sisal fiber is 0.5%-1% of the geopolymer fully recycled concrete.

[0030] Furthermore, the water reducer is a polycarboxylate water reducer with a water reduction efficiency of 20-25%; and the retarder is a FK-6 type composite retarder.

[0031] A second aspect of the present invention provides a method for preparing geopolymer-based fully recycled concrete, the method comprising the following steps:

[0032] 1) Mix blast furnace slag, recycled powder, alkali activating liquid, water reducing agent and retarder and stir them once to obtain a binder;

[0033] 2) Add recycled fine aggregate, sisal fiber and water and stir for a second time;

[0034] 3) adding recycled coarse aggregate and stirring three times to obtain fresh concrete;

[0035] 4) Pour the freshly mixed concrete in step 3) into a mold, vibrate and compact it, and then place it in a standard curing environment for curing to obtain geopolymer-based fully recycled concrete.

[0036] Furthermore, in step 1), during the first stirring, the stirring speed is 120-150 rpm, and the stirring time is 30-40 s; in step 2), during the second stirring, the stirring speed is 120-150 rpm, and the stirring time is 30-40 s.

[0037] Furthermore, in step 3), during the three stirrings, the stirring speed is 60-80 rpm and the stirring time is 120-130 seconds, so that all materials are mixed evenly.

[0038] Furthermore, the uniform distribution of the sisal fibers is achieved by first mixing the binder, the sisal fibers and the recycled fine aggregate and then adding the recycled coarse aggregate and mixing again.

[0039] Furthermore, in step 4), in the standard curing environment, the temperature is 18-22° C. and the relative humidity is above 95%. During the curing, the curing process is specifically as follows: the vibrated and compacted concrete is placed in a standard curing environment for curing for 1 day before demolding, and then the demolded sample is placed in a standard curing room for continued curing for 28 days or more.

[0040] Furthermore, the pouring, vibrating and curing methods of the fresh concrete are the same as those of conventional concrete.

[0041] Compared with the prior art, the present invention has the following characteristics:

[0042] 1) The present invention uses recycled coarse and fine aggregates to replace natural sand and gravel aggregates, uses a mixture of slag and recycled powder as an alkali-activated precursor, and adds short-cut sisal fibers to ensure the toughness and crack resistance of concrete;

[0043] 2) The concrete mix ratio of the present invention regulates the amount and length of the short-cut sisal fibers based on different mechanical properties and thermal insulation requirements. By adding sisal fibers of different amounts and lengths, the tensile strength, crack resistance and low thermal conductivity of the sisal fibers are brought into play, so as to achieve the purpose of strengthening, toughening and reducing thermal conductivity, and the recycled concrete powder partially replaces the slag in the precursor to improve the utilization rate of the recycled components;

[0044] 3) The present invention provides an application scheme that can effectively dispose of construction solid waste and recycle a large amount of recycled concrete powder and sisal fiber to prepare geopolymer fully recycled concrete. It mainly focuses on the construction of "zero-waste cities", increases the utilization efficiency of construction waste and industrial solid waste, and creates low-carbon and low-thermal conductivity concrete, which has a relatively broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The present invention is a schematic diagram of a method for preparing a low-carbon and low-thermal-conductivity geopolymer-based fully recycled concrete. DETAILED DESCRIPTION

[0046] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0047] Figure 1 The present invention is a schematic flow chart of a method for preparing a low-carbon and low-thermal-conductivity geopolymer-based fully recycled concrete. The method for preparing the geopolymer-based fully recycled concrete in the following embodiment specifically comprises the following steps:

[0048] Step 1: Grinding and screening to obtain recycled concrete powder

[0049] 5-10mm single-grained recycled coarse aggregate and 0.15-2.36mm recycled fine aggregate produced by a waste concrete processing plant are selected, the recycled coarse aggregate is ground and then sieved through a sorting machine to obtain powder with a particle size of less than 75μm to obtain recycled powder, which is stored as one of the alkali-activated precursors.

[0050] Step 2: Prepare the alkaline stimulating solution

[0051] Sodium hydroxide solid with a purity of 98% was dissolved in deionized water to prepare a sodium hydroxide solution with a concentration of 10 mol / L. After the sodium hydroxide solution was cooled down by exothermic heating, the sodium hydroxide solution was mixed with water glass with a modulus of 3.3 (mass ratio, Na 2 O=8.54%,SiO 2 =27.30%, H 2 The alkali stimulating solution was prepared 24 hours before use and sealed for storage.

[0052] Step 3: Cutting the Sisal Fiber

[0053] The sisal fibers were placed in a fiber cutter and cut into short sisal fibers of 5 mm, 10 mm and 20 mm, and stored separately for later use.

[0054] Step 4: Mix design of sisal fiber geopolymer fully recycled concrete

[0055] According to the basic performance requirements of geopolymer fully recycled concrete, the precursor is considered to use 90% blast furnace slag and 10% recycled powder in the mix design;

[0056] According to the mechanical and thermal insulation performance requirements of concrete in different usage scenarios, the sisal fiber content in the mix design is considered to be 0.5%-2% of the concrete volume;

[0057] The raw materials weighed mainly include: blast furnace slag, recycled powder, recycled fine aggregate, recycled coarse aggregate, sisal fiber, water glass (sodium silicate aqueous solution, Na 2 O.nSiO 2), sodium hydroxide solution, water, water reducer, retarder; the raw materials weighed (in parts by mass) are: 450 parts of blast furnace slag, 50 parts of recycled powder, 460 parts of recycled fine aggregate, 935 parts of recycled coarse aggregate, 4.65-18.6 parts of sisal fiber, 135 parts of water glass, 90 parts of sodium hydroxide solution, 90-118 parts of water, 8 parts of water reducer, and 2 parts of retarder.

[0058] Step 5: Preparation of sisal fiber geopolymer fully recycled concrete:

[0059] Add blast furnace slag, recycled powder and alkali activating liquid to the mixer in sequence, add water reducer and retarder, and stir at high speed for 30 seconds. Then add recycled fine aggregate, chopped sisal fiber and additional water, and stir at high speed for another 30 seconds. After stirring evenly, add recycled coarse aggregate and continue stirring at medium or low speed for 120 seconds until the fiber is evenly dispersed. Pour the fresh concrete into the mold and place it on a vibrating table to vibrate and compact it.

[0060] Step 6: Demolding and maintenance:

[0061] The prepared molded specimens were cured in a standard curing room for 1 day and then demolded. The demoulding specimens were then placed in a standard curing room and cured for 28 days to obtain the above-mentioned geopolymer fully recycled concrete.

[0062] The following are more detailed implementation cases, which further illustrate the technical solutions of the present invention and the technical effects that can be obtained.

[0063] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.

[0064] In the following examples and comparative examples, the blast furnace slag is S95 grade ore powder with a density of ≥2800kg / m 3 , meeting the requirements of GB / T18046-2008 "Granulated blast furnace slag powder for cement and concrete"; the recycled powder meets the requirements of JG-T 573-2020 "Recycled micro powder for concrete and mortar"; the recycled fine aggregate meets the requirements of GB / T25176-2010 "Recycled fine aggregate for concrete and mortar", the recycled coarse aggregate is a single-grade recycled concrete aggregate, meeting GB / T 25177-2010 "Recycled coarse aggregate for concrete"; the sisal fiber meets the requirements of GB / T15031-2009 "Sisal fiber"; the sodium hydroxide is analytical grade; the water is ordinary tap water, the temperature is ≤30℃; the water reducer is a polycarboxylic acid water reducer, meeting the requirements of GB 50119-2013 "Technical Specifications for Application of Concrete Admixtures"; the retarder is an FK-6 type composite retarder, meeting the requirements of GB 8076-2008 "Concrete Admixtures".

[0065] Embodiment 1:

[0066] A geopolymer-based fully recycled concrete containing 0.5% by volume of 10 mm sisal fiber, the preparation method of which comprises the following steps:

[0067] 1) Select 450 parts of blast furnace slag, 50 parts of recycled powder, 225 parts of alkali activating solution (135 parts of water glass + 90 parts of sodium hydroxide solution), 8 parts of water reducing agent, and 2 parts of retarder, add them into a mixer, and stir at a high speed of 150r / min for 30s;

[0068] 2) Slowly add 460 parts of recycled fine aggregate, 4.65 parts of 10 mm sisal fiber, and 97 parts of water into the mixer, and stir at a high speed of 150 r / min for 30 seconds until the above components are evenly mixed;

[0069] 3) Slowly add 935 parts of recycled coarse aggregate into the mixer and stir at a medium-low speed of 80 r / min for 120 s until all the materials are evenly mixed;

[0070] 4) The prepared sisal fiber geopolymer fully recycled concrete molded sample was cured in a standard curing room for 1 day and then demolded, and then the demolded sample was placed in a standard curing room for further curing for 28 days to obtain a geopolymer fully recycled concrete containing 0.5% by volume of 10 mm sisal fiber.

[0071] Embodiment 2:

[0072] A geopolymer fully recycled concrete containing 10 mm sisal fiber with a concrete volume content of 1%, the preparation method of which is different from that of Example 1, except that: in step 2), 4.65 parts of 10 mm sisal fiber and 97 parts of water are replaced with 9.3 parts of 10 mm sisal fiber and 104 parts of water. The remaining steps are the same as those of Example 1. A geopolymer fully recycled concrete containing 1% of 10 mm sisal fiber with a volume content of 1% is obtained.

[0073] Embodiment 3:

[0074] A geopolymer fully recycled concrete containing 10 mm sisal fiber with a concrete volume content of 2%. The preparation method thereof is different from that of Example 1, except that in step 2), 4.65 parts of 10 mm sisal fiber and 97 parts of water are replaced with 18.6 parts of 10 mm sisal fiber and 118 parts of water. The remaining steps are the same as those of Example 1. A geopolymer fully recycled concrete containing 2% by volume of 10 mm sisal fiber is obtained.

[0075] Embodiment 4:

[0076] A geopolymer fully recycled concrete containing 5mm sisal fiber with a concrete volume content of 1%, the preparation method of which is different from that of Example 1, except that in step 2), 4.65 parts of 10mm sisal fiber and 97 parts of water are replaced with 9.3 parts of 5mm sisal fiber and 104 parts of water. The remaining steps are the same as those of Example 1. A geopolymer fully recycled concrete containing 1% of 5mm sisal fiber by volume is obtained.

[0077] Embodiment 5:

[0078] A geopolymer fully recycled concrete containing 1% of 20 mm sisal fiber by volume of concrete, the preparation method of which is different from that of Example 1, except that in step 2), 4.65 parts of 10 mm sisal fiber and 97 parts of water are replaced with 9.3 parts of 20 mm sisal fiber and 104 parts of water. The remaining steps are the same as those of Example 1. A geopolymer fully recycled concrete containing 1% of 20 mm sisal fiber by volume is obtained.

[0079] Comparative Example 1:

[0080] A geopolymer fully recycled concrete without sisal fiber, the preparation method thereof is different from that of Example 1, except that: in step 2), 4.65 parts of 10 mm sisal fiber and 97 parts of water are replaced with 90 parts of water. The remaining steps are the same as those of Example 1. A geopolymer fully recycled concrete without sisal fiber is obtained.

[0081] The above examples 1-5 respectively prepared geopolymer recycled concrete containing 0.5% by volume of 10mm sisal fiber, geopolymer recycled concrete containing 1% by volume of 10mm sisal fiber, geopolymer recycled concrete containing 2% by volume of 10mm sisal fiber, geopolymer recycled concrete containing 1% by volume of 5mm sisal fiber, and geopolymer recycled concrete containing 1% by volume of 20mm sisal fiber. Comparative example 1 prepared geopolymer recycled concrete without fiber. The test results are shown in Table 1. Compared with comparative example 1, the geopolymer recycled concrete in examples 1-5 is 2 The emissions were reduced. When 1% by volume of 5 mm sisal fiber was added (Example 4), the thermal conductivity of geopolymer recycled concrete decreased by 14%, CO 2The emission decreased by 6%, and the mechanical properties were comparable. Compared with the comparative example, the thermal conductivity of Example 3 and Example 5 increased. This is because the addition of too much (2%) or too long (20mm) sisal fiber will increase the number of macropores connected inside the concrete, which is not conducive to its thermal insulation. The mechanical properties and thermal insulation properties of the geopolymer fully recycled concrete prepared in the above Examples 1-5 and Comparative Example 1 were respectively carried out in accordance with the requirements of GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete" and GB / T 10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials".

[0082] Table 1

[0083]

[0084]

[0085] The above embodiment uses recycled coarse and fine aggregates to replace natural sand and gravel aggregates, uses slag and recycled powder mixed as alkali-activated precursors, and adds sisal fibers of different dosages and lengths, with the purpose of strengthening, toughening, and reducing thermal conductivity, and giving full play to the tensile strength, crack resistance and low thermal conductivity of sisal fibers. Sisal fibers have the characteristics of low cost and low carbon. Sisal fibers fix carbon through photosynthesis during their growth cycle, and recycled aggregates have good carbon absorption capacity during the storage stage. The two are used in synergy to create a low-carbon building material. In addition, both recycled concrete and geopolymer concrete have significant advantages in low thermal conductivity, and the addition of fibers also has a significant effect on the thermal performance of concrete. Sisal fibers have a low thermal conductivity, and combined with geopolymer fully recycled concrete, the thermal conductivity of concrete is further reduced, thereby improving the energy-saving effect of buildings, focusing on the construction of "zero-waste cities", increasing the utilization efficiency of construction waste and industrial solid waste, and creating low-carbon and low-thermal conductivity concrete.

[0086] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A geopolymer-based fully recycled concrete, characterized in that: The geopolymer-based fully recycled concrete includes the following components and their contents by weight:

2. The geopolymer-based fully recycled concrete according to claim 1, characterized in that: The alkaline activating solution comprises water glass and sodium hydroxide solution, the mass ratio of the sodium hydroxide solution to the water glass is 2:3; the modulus of the water glass is 3.3; and the concentration of the sodium hydroxide solution is 10 mol / L.

3. The geopolymer-based fully recycled concrete according to claim 1, characterized in that: The blast furnace slag is S95 grade ore powder with a density of ≥2800kg / m 3 .

4. The geopolymer-based fully recycled concrete according to claim 1, characterized in that: The recycled powder and recycled fine aggregate are powders obtained by grinding and screening recycled concrete aggregates. The particle size of the recycled powder is ≤0.075mm, the particle size of the recycled fine aggregate is 0.15-2.36mm; and the particle size of the recycled coarse aggregate is 5-10mm.

5. The geopolymer-based fully recycled concrete according to claim 1, characterized in that: The sisal fibers are short-cut sisal fibers, and the length of the sisal fibers is 5-20 mm; the tensile strength of the sisal fibers is ≥600 MPa, and the elastic modulus is ≥30 GPa.

6. The geopolymer-based fully recycled concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent with a water reducing efficiency of 20-25%; the retarder is a FK-6 type composite retarder.

7. The method for preparing geopolymer-based fully recycled concrete according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: 1) Mix blast furnace slag, recycled powder, alkali activating liquid, water reducing agent and retarder and stir them once to obtain a binder; 2) Add recycled fine aggregate, sisal fiber and water and stir for a second time; 3) adding recycled coarse aggregate and stirring three times to obtain fresh concrete; 4) Pour the freshly mixed concrete in step 3) into a mold, vibrate and compact it, and then place it in a standard curing environment for curing to obtain geopolymer-based fully recycled concrete.

8. The geopolymer-based fully recycled concrete according to claim 7, characterized in that: In step 1), during the first stirring, the stirring speed is 120-150 rpm, and the stirring time is 30-40 s; in step 2), during the second stirring, the stirring speed is 120-150 rpm, and the stirring time is 30-40 s.

9. The geopolymer-based fully recycled concrete according to claim 7, characterized in that: In step 3), during the three stirrings, the stirring speed is 60-80 rpm and the stirring time is 120-130 s.

10. The geopolymer-based fully recycled concrete according to claim 7, characterized in that: In step 4), the temperature in the standard curing environment is 18-22° C. and the relative humidity is above 95%. During the curing, the curing process is as follows: the vibrated and compacted concrete is placed in the standard curing environment for curing for 1 day, then the mold is removed, and then the demolded sample is placed in a standard curing room for further curing for 28 days or more.

Citation Information

Cited By

  • All-recycled aggregate geopolymer toughness reinforced concrete pipe based on functional gradient design and microcapsule self-healing and preparation method of all-recycled aggregate geopolymer toughness reinforced concrete pipe

    CN122345184A